Penggunaan Metode Pembelajaran Inside-Outside Circle untuk Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam (Penelitian Tindakan Kelas di Kelas V Sekolah Dasar Negeri 4 Cintanagara, Jatinagara, Kabupaten Ciamis) - Angrawati, Weni; Al Hamdani, M. Djaswidi (Jurnal Penelitian Pendidikan Islam, 2018)
This classroom action research aims to improve the quality of learning Islamic Education subjects. The results showed that (1) through the Inside-Outside Circle learning method, the teacher managed to improve the quality of the learning planning system; (2) through the Inside-Outside Circle learning method, teachers also have the ability to improve the quality of learning implementation; and (3) through the Inside-Outside Circle learning method, student learning outcomes in Islamic Education subjects also experienced a significant increase, namely from the first cycle which averaged a score of 72, increased to 80.3 in the second cycle. And in the last cycle the score of student learning outcomes increases to 85.